PENGARUH WARNA PADA MEDIA KOMPUTER POWERPOINT DALAM MENINGKATKAN PENGETAHUAN PETERNAK DI KTT SAPI PERAH “SIDODADI” DI KECAMATAN GETASAN KABUPATEN SEMARANG - R. A. Rahma; W. Sumekar; S. Dwijatmiko (JURNAL LITBANG PROVINSI JAWA TENGAH, 2016)
The objective of this study is to analyze the increase in fodder correct knowledge on dairy farmers by providing the fodder correct education, to analyze the differences in the increase of knowledge based on the color presentation slide, and to analyze the effect on the improvement of knowledge based on the color peresentation slide and the repetition. The research method that is used in this study is the experimental method of pre-test and post-test. Respondents are 20 dairy farmers obtained from members of the KTT Sidodadi using survey methods. There are 2 treatments, the color presentation and the colorless presentation. The Knowledge of feeding is measured by using a written test. The objective test ‘true or false’ test is used in the written test. The obtained data is analyzed by independent t test, Univariate F t test and Duncan with SPSS 16.0 program. The results of this study shows that there is a relatively high increase in knowledge. The increased knowledge on color media has a significant difference to the significant value of 0.000. From the data analysis, it can be concluded that the color in the media give a good effect in increasing knowledge of dairy farmers with sig 0.000. Whereas, the repetition does not give an effect in the increase of knowledge.